Behavior of Magnetically-Driven Concrete (MDC) Filled Double-Skin GFRP Tubes (CFDGT) Under Axial Compression - Xie, Xian-Song; Chen, Ju; Wang, Jun; Liu, Cheng-Bin (Frontiers in Built Environment, 2022)
In order to study the axial compression behavior of magnetically-driven concrete (MDC) filled double-skin GFRP tubes (CFDGT), the axial compression test was conducted on 8 columns (the length of columns ranged from 1000 mm to 3000 mm). For the MDC, a magnetic vibration device was established to vibrate the MDC, and two series of MDC (concrete with and without vibration) were adopted to investigate the vibration effect, research results showed that the concrete between two circular GFRP tubes could be effectively vibrated by the magnetic force. For the CFDGT columns with MDC, the load-displacement curves, load-strain curves, failure modes and ultimate loads of tested columns were obtained. After the axial compression test, a finite element model was proposed to predict the axial compression behavior and carry out parametric analysis. The design equations for the ultimate load of CFDGTs were derived from the finite element results, comparison results showed that the design equations can predict the ultimate load of CFDGT columns accurately and conservatively, and the maximum calculation error was controlled within 10%.